2011
DOI: 10.1176/appi.ajp.2011.10081209
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Neurocognition on Social and Role Functioning in Individuals at Clinical High Risk for Psychosis

Abstract: Objective Cognitive deficits have been well documented in schizophrenia and have been shown to impair quality of life and to compromise everyday functioning. Recent studies of adolescents and young adults at high risk for developing psychosis show that neurocognitive impairments are detectable before the onset of psychotic symptoms. However, it remains unclear how cognitive impairments affect functioning before the onset of psychosis. The authors assessed cognitive impairment in adolescents at clinical high ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
144
2
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 171 publications
(168 citation statements)
references
References 42 publications
16
144
2
6
Order By: Relevance
“…Studies with psychosis at-risk groups report evidence of both neurocognitive deficits and declines in functioning up to 10 years prior to clinical diagnosis (Bachman et al, 2012;Seidman et al, 2006). Cognitively, this includes reduced processing speed (Carrión et al, 2011;Carrion et al, 2015), impairments in attention (Carrion et al, 2015;Myles-Worsley et al, 2007) and executive function (Carrion et al, 2015). As already noted, some of these deficits were present in our sample.…”
Section: Vocational Functioning Neurocognitive Outcomes and Associatsupporting
confidence: 69%
“…Studies with psychosis at-risk groups report evidence of both neurocognitive deficits and declines in functioning up to 10 years prior to clinical diagnosis (Bachman et al, 2012;Seidman et al, 2006). Cognitively, this includes reduced processing speed (Carrión et al, 2011;Carrion et al, 2015), impairments in attention (Carrion et al, 2015;Myles-Worsley et al, 2007) and executive function (Carrion et al, 2015). As already noted, some of these deficits were present in our sample.…”
Section: Vocational Functioning Neurocognitive Outcomes and Associatsupporting
confidence: 69%
“…Smith and colleagues 135 have also shown spatial working memory deficits in an American sample of 8 UHR patients. Hawkins and colleagues 136 demonstrated verbal working memory deficits on a letter-number sequencing task in a sample of 36 Canadian and American UHR patients, a finding recently replicated by Carrion and colleagues 137 in a larger sample of UHR patients (n 5 127) also using the letter-number sequencing task.…”
Section: Working Memorymentioning
confidence: 83%
“…Most recently, Carrion and colleagues 137 have also shown in a large sample of American UHR patients that not only were processing speed deficits especially pronounced relative to most other neurocognitive deficits but also processing speed deficits were uniquely predictive of social and role functioning, independent of positive psychotic symptoms. This is interesting given that some researchers have suggested that symbol-coding deficits reflect the core of schizophrenia neurocognitive impairment.…”
Section: Processing Speedmentioning
confidence: 95%
See 2 more Smart Citations